Crecimiento y productividad de ricino de baja altura en diferentes espaciamientos entre hileras y poblaciones de plantas - De Souza-Schlick, Genivaldo David [UNESP]; Soratto, Rogério Peres [UNESP]; Bottino, Douglas [UNESP]; Fernandes, Adalton Mazetti [UNESP] (My University, 2012)
It is necessary to establish adequate row spacings and plant populations for recently developed short height castor (Ricinus communis L.) cultivars. This work aimed to evaluate the growth, yield components, and yield of short castor cultivar IAC 2028 as affected by row spacing and plant population, in summer cropping season. The experiments were carried out in 2007/08 and 2008/09 cropping seasons, in Botucatu County, São Paulo State, Brazil. A randomized complete block design in a split-plot scheme with four replications was used. Treatments assigned to plots were four row spacing (0.45, 0.60, 0.75, and 0.90m) and subplots were assigned to four levels of plant populations (25000, 40000, 55000, and 70000 plants/ha). The increase of plant population decreased plants survival rate, shoot dry weight, stem diameter, number of racemes per plant, number of fruits per raceme, and 100-grains weight. In higher plant populations, the best arrangement of plants, provided by the narrower row spacing (0.45m), promoted higher grain and oil yields. Increasing plant population increased grain and oil yields only when was used the narrower row spacing.
Growth and yield of short height castor on differentrow spacings and plant populations